The vulnerability level and employee preparedness index in responding to fire in mills division at pt. eastern pearl flour mills of Makassar city - Andi Akram Al Qadri; Hasbi Ibrahim; Syamsul Alam (Universitas Islam Negeri Alauddin Makassar, 2020)
BNPB (The National Agency for Disaster Countermeasure) suggested that there were 3,193 cases of fires in Indonesia from 1815 to 2018. There were 6 cases of fires at PT. Eastern Pearl Flour Mills during the period of 2016 to 2019 which resulted in material loss. The main objective of this study was to investigate and determine the level of fire vulnerability and employee preparedness index at Mills division at PT. Eastern Pearl Flour Mills of Makassar. The methodological approach taken was descriptive by using a survey method. The population were all 38 employees. The sampling technique was total sampling. The samples used in this study were 38 samples. The results indicated that in the aspect knowledge, 38 respondents high category (100%). Attitude, 38 respondents (100%) high category. Disaster preparedness policy, 35 respondents (92.1%) high category, and 3 respondents (7.9%) low category. Resource mobilization, 36 respondents (94.7%) high category, and 2 respondents (5.3%) low category. Disaster warning, 38 respondents (100%) high category.Preparedness plan, 33 respondents (86.8%) high category, and 5 respondents (13.2%) low category. This research concludes that the level of fire vulnerability at the Mills division at PT. Eastern Pearl Flour Mills Makassar City was considered the medium category, while the employee preparedness index was considered in the fair category. The researchers suggest the company to continous socialization related to fire prevention SOPs to all employees. The employees must be able to distinguish signs of the fire warning and increase their knowledge related to fire disasters in the workplace.